2021
DOI: 10.3390/met11081329
|View full text |Cite
|
Sign up to set email alerts
|

Reductions of Intergranular Corrosion Resistance and Wear Resistance in a Ni-Cr-Mo-Based Superalloy by Aging-Treatment-Induced Precipitation

Abstract: Ni-Cr-Mo-based superalloy is widely used as a key component in many critical environments. To ensure that the manufacturing process does not impact the long-term service performance of these components, the aging precipitation behavior at different temperatures and its effect on intergranular corrosion (IGC) resistance and wear resistance of a Ni-Cr-Mo-based C276 superalloy were investigated. The equilibrium phase diagram was calculated first using thermodynamic software to confirm the potential phases. Carbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The wear performance of a material can also be affected by its microstructure. Zhang and co-authors [10] studied the influence of aging treatment on the corrosion and wear resistances of a Ni-Cr-Mo-based C276 superalloy. It was found that the presence of precipitates at grain boundaries due to aging resulted in increases in the friction coefficient, the fluctuations in the friction coefficient during steady-state sliding wear process and also the wear track dimensions.…”
Section: Contributionsmentioning
confidence: 99%
“…The wear performance of a material can also be affected by its microstructure. Zhang and co-authors [10] studied the influence of aging treatment on the corrosion and wear resistances of a Ni-Cr-Mo-based C276 superalloy. It was found that the presence of precipitates at grain boundaries due to aging resulted in increases in the friction coefficient, the fluctuations in the friction coefficient during steady-state sliding wear process and also the wear track dimensions.…”
Section: Contributionsmentioning
confidence: 99%